2019
DOI: 10.31883/pjfns/112019
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Phenolic Compounds Profile and Antioxidant Activity in Different Parts of Hawthorn (Crataegus pentagyna Willd.) During Harvest Periods

Abstract: are the most important species in China, whereas Crataegus laevigata Poir. (syn: Crataegus oxyacantha L.), Crataegus monogyna Jacq., Crataegus pentagyna Waldst., Crataegus nigra Waldst., and Crataegus azarolus L. are the major species in Europe [Rayyan et al., 2005; Liu et al., 2011]. Crataegus species have long been used in traditional Chinese and European herbal medicine. In addition to being highly recommended in folk medicine, hawthorn berries are valuable food ingredient due to the content of nutrients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…Extraction time was lower than reported in a previous study that reported 1.5 h to obtain a maximum yield of flavonoids from hawthorn seed, which was 16.45 ± 0.02 mg/g d.w. obtained at a solvent-to-solid ratio of 18 (v/w) and 72% ethanol [23]. A previous study reported a similar total phenolic content in C. pentagyna (98.3-107 and 128 mg GAE/g d.w.), which was extracted by maceration (0.2 g of leaves with 15 mL of 80% acetone for 48 h) followed by an ultrasound-assisted extraction of 15 min with 10 mL of 80% acetone, five successive times [11]. The total phenolic content obtained in C. monogyna leaf extract at optimum conditions was in the magnitude order than a previous study in an extract of C. orientalis leaves, which was 94.2 mg GAE/g d.w.…”
Section: Optimization Of Ultrasonic-assisted Extractionmentioning
confidence: 75%
See 2 more Smart Citations
“…Extraction time was lower than reported in a previous study that reported 1.5 h to obtain a maximum yield of flavonoids from hawthorn seed, which was 16.45 ± 0.02 mg/g d.w. obtained at a solvent-to-solid ratio of 18 (v/w) and 72% ethanol [23]. A previous study reported a similar total phenolic content in C. pentagyna (98.3-107 and 128 mg GAE/g d.w.), which was extracted by maceration (0.2 g of leaves with 15 mL of 80% acetone for 48 h) followed by an ultrasound-assisted extraction of 15 min with 10 mL of 80% acetone, five successive times [11]. The total phenolic content obtained in C. monogyna leaf extract at optimum conditions was in the magnitude order than a previous study in an extract of C. orientalis leaves, which was 94.2 mg GAE/g d.w.…”
Section: Optimization Of Ultrasonic-assisted Extractionmentioning
confidence: 75%
“…Hawthorn fruits, leaves and flowers contain phenolic compounds such as flavone and flavonol glycosides, hydroxycinnamic acids, flavan-3-ols (especially (−)-epicatechin) and flavan-3-ol oligomers (B-type procyanidins). [7][8][9][10][11]. Flavan-3-ols (epicatechin), flavonols (hyperoside) and hydroxycinnamic acids such as chlorogenic acid and protocatechuic acid are dominant in leaves [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of phenolic compounds in the main morphological parts of sunflowers and the confirmed biological activity of some of them make it possible to assume that green sunflower plants can be regarded, not only as a valuable feed constituent, but also as a source of natural antioxidants. Since the profile of secondary metabolites may change during plant growth [28,29], it seems necessary to consider plants harvested at various growth stages. The aim of this study has therefore been to determine the phenolic compound profile and in vitro antioxidant activity of extracts obtained from the aerial parts of sunflowers harvested at five growth stages, from stem extension to late flowering, to find those that are promising sources of phenolic antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…It seems important to complete our knowledge about the phenolic compounds of the aerial part of C. sativa, especially because of the ever-growing interest in this plant [Faure & Tepfer, 2016]. The composition of the phenolic compounds changes during the growth cycle of plants [Gai et al, 2017;Karamać et al, 2019;Pavlović et al, 2019], therefore, the purpose of our research has been to determine the phenolic compound profi le and antioxidant potential of the aerial part of false fl ax at several morphological stages, that is, from the vegetative to the ripe seed-pod stage, in order to select those with the highest parameters as a potential source of phenolic antioxidants.…”
Section: Introductionmentioning
confidence: 99%